Of droughts, famines, plagues and "other various and continuous calamities that occurred in the jurisdiction of Córdoba" during the 18th century. - Prieto, María del Rosario; Herrera, Roberto Gustavo (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2001)
Our work is precisely focused on studying the variations in rainfall throughout the eighteenth century in Cordoba and evaluating its impact on the economy and colonial society, continuing with the approaches to the subject made from other perspectives by Cordovan authors. We will consider the climatic variations of medium and long duration, also incorporating, as far as possible, those of shorter range.